Protective Effect of Cuminum cyminum and Coriandrum sativum on Profenofos Induced Liver Toxicity - Kumar, Arun (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT In recent years there is an immense pressure on farmers to harvest more grains for growing population. For higher production they are extensively using the pesticides which are hazardous to human health. As such, it becomes necessary to evaluate the effect of these pesticides on human health and search for a subsequent protective agent against there hazardous effects. In the present investigation an organophosphate (profenofos) was administered @ 25mg/Kg b.w for 30 days to swiss albino mice to observe its effect on liver. Further, Cuminum cyminum and Coriandrum sativum extracts were administered to the profenofos intoxicated group @ 100mg/Kg b.w and 1000 mg/Kg b.w respectively for 30 days to evaluate their protective efficacy. An elevated level of liver function test (LFT) was observed in profenofos intoxicated group in comparison to the control. However, the two antidotes administered group showed decreasing trend of LFT. The finding suggests the vital role of the plant extracts in reducing the hepatotoxicity at the cellular and biochemical levels. Of the two medicinal plants, cumin was found to be more effective for its hepato-protective role than that of Coriander. Key words: Liver, Profenofos, Cuminum cyminum and Coriandrum sativum, LFT, Swiss albino mice.